STRATEGI INOVASI BUMDES DALAM MENINGKATKAN POTENSI DAN KESEJAHTERAAN EKONOMI MASYARAKAT PESISIR KABUPATEN SELUMA DENGAN METODE CRITERIUM PLUS - AHP - Kresnawati Kresnawati; Siti Hanila (Management Insight: Jurnal Ilmiah Manajemen, 2019)
This research was conducted in order to obtain the best innovation strategy for Village-Owned Enterprises (BUMDES) to improve the economic welfare of the coastal communities of Sukasari, Lawang Agung and Kunkai Baru, Seluma Regency. Mapping analysis of potentials and problems that occur in BUMDES in coastal areas is done by using the Focus Group Discussion (FGD) method through SWOT analysis techniques and Criterium Plus - Analytical Hierarchy Process analysis. The results of the study show that there are 4 priority problems that occur in existing BUMDES, namely the problem of weak financial governance, weak BUMDES management, limited marketing access, and the similarity of the BUMDES business field to other BUMDES. Problem solving strategies can be carried out through efforts to build marketing networks, business feasibility studies through BUMDES health checks and build synergies with local governments.